Knowledge and Attitude of Extension Educators Towards Digitising Agricultural Extension Services in Kwara State, Nigeria - Makinde, Oluwafunmilola; Abidemi, Adeosun; Ogunlade, Israel; Oladele, Oladimeji; Shuaib, Abdulganiyu (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
This study assessed the knowledge, attitudes and constraints of agricultural extension educators regarding the integration of digital tools in agricultural extension services in Kwara State, Nigeria, by examining the extent to which extension educators are knowledgeable about and favourably disposed to using digital tools in agricultural extension services, as well as ascertaining the barriers to their effective adoption. A survey design was employed using a two-stage sampling technique. Data were collected via a structured interview schedule and analysed using descriptive statistics. The results showed that 57% of respondents were male, 71% were married and 40% held PhDs – with a mean age of 45.3 years and 11.3 years of teaching experience. A significant majority (77%) demonstrated high knowledge and a favourable attitude towards digital extension services. Although 82% were aware of digital tools, only 48.2% reported high usage. The main constraints were poor orientation, high internet connectivity costs and the expense of digital equipment. Correlation analysis indicated a statistically significant relationship between digital literacy and willingness to adopt digital extension tools (r = 0.72, p < 0.05), emphasising the role of technical capacity-building in accelerating adoption. These findings underscore the need for targeted capacity-building, financial incentives and infrastructure improvements to enhance digital adoption in agricultural extension services.